A multiple criteria evaluation of a new streets development projects in Vilnius city - Jakimavičius, Marius; Burinskienė, Marija; Gusarovienė, Modesta (International Conference “Environmental Engineering”, 2017)
The paper considers the technological development of a new streets equipment in Vilnius street network. All main transport infrastructure projects in Vilnius city are presented and analyzed with reference to the selected system of transport projects assessment criteria. This article describes the situation and progress of the main streets development projects in Vilnius and shows the influence for whole Vilnius city transportation system. The paper also analyses parameters for infrastructure projects for the multiple attribute ranking of a new streets development or reconstruction in Vilnius city. Multi-criteria methods have been chosen to rank three projects and to estimate the best and most effective transport network object based on the preferred technological, transportation operational and financial data. The experts of different decision-making groups have analyzed the importance of parameters selected for assessing alternatives of a new Vilnius city streets development projects ranking. The experts on the transport system have been invited to determine the relative weights of the defined criteria. Two techniques, including, SAW (Simple Additive Weighting) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) methods have been used and compared to determine the most efficient project based on economic and technological parameters. To rank alternatives and to make a comparison of the obtained calculation results, two multi-criteria methods have been applied in this research.